Invasive hemodynamics of constrictive pericarditis - Shrenik Doshi (Indian Heart Journal, 2015)
Cardiac catheterization and hemodynamic study is the gold standard for the diagnosis of pericardial constriction. Careful interpretation of the hemodynamic data is essential to differentiate it from other diseases with restrictive physiology. In this hemodynamic review we shall briefly discuss the physiologic basis of various hemodynamic changes seen in a patient with constrictive pericarditis.